(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Pulmonary embolism (PE) is a potentially life-threatening condition resulting from the obstruction of pulmonary arteries, most commonly by thrombi originating from the deep veins of the lower limbs. In recent years, a notable rise in PE incidence has been observed globally, attributed to both improved detection and an increase in predisposing risk factors. Objective: To provide a comprehensive overview of the evolving epidemiology, diagnostic approach, clinical features, therapeutic options, and long-term outcomes of PE, with emphasis on the critical rise in incidence and implications for clinical practice. Methods: A narrative review was conducted using recent peer-reviewed literature and guideline-based recommendations. Studies were selected from indexed databases focusing on diagnostic algorithms, imaging modalities, treatment outcomes, and epidemiological trends related to acute PE. Results: PE incidence is increasing globally, driven by aging populations, cancer survivorship, and postoperative complications. Clinical presentation varies widely, often mimicking other cardiopulmonary conditions, making early diagnosis challenging. Risk stratification tools such as the Wells score, revised Geneva score, and Pulmonary Embolism Severity Index (PESI) are critical in guiding the use of D-dimer testing and imaging. Computed tomography pulmonary angiography (CTPA) remains the diagnostic gold standard. Treatment strategies are guided by risk categories—ranging from anticoagulation alone in low-risk cases to thrombolysis or surgical embolectomy in high-risk cases. Long-term complications such as chronic thromboembolic pulmonary hypertension (CTEPH) and post-PE syndrome significantly impact quality of life, underscoring the importance of follow-up and rehabilitation. Conclusion: The increasing incidence and variable presentation of PE demand heightened clinical vigilance. Early risk-adapted diagnosis and intervention are pivotal in reducing mortality and morbidity. Long-term monitoring and individualized therapy are essential for improving patient outcomes. Future strategies should emphasize prevention, early detection, and research into novel diagnostic and therapeutic tools.